PENDIDIKAN ANAK DALAM KELUARGA - Asriana Harahap; Mhd. Latip Kahpi Nasution (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Children's education in the perspective of the Qur'an must lead to the formation of pious children. Efforts to form godly children require struggle and patience. One way that God can do is to imitate the Apostles and pious people in educating their children; for example Luqman al-Hakim and Nabiyullah Ibrahim AS. This is done so that children and the next generation as bearers of future life are not in a weak condition, which is low moral and intellectual.Education in Luqman al-Hakim's family emphasizes four aspects of life, namely: aqeedah, worship, morality, and da'wah. Meanwhile, Ibrahim educates his children so that: First, Ibrahim trains and educates their children to give their views and opinions on a problem faced together in the family. Second, Ibrahim educates his son Ismail, his favorite child in a dialogically democratic way. Third, Ibrahim US teaches openness to his child. Fourth, Ibrahim educates his children to have courage. Fifth, Ibrahim educates his child to have a willingness to sacrifice even if the sacrifice is his own soul. Sixth, Ibrahim educates his children to be obedient to Allah SWT by only worshiping Him alone. Seventh, Ibrahim educates his children in addition to being obedient and obedient to God as well as to both parents. Eighth, Ibrahim educates his child to be a child who has self-confidence (self confidence). Ninth, Ibrahim educates his child to be a patient child. There are at least six situations where one must be patient, namely: (1) patience with the disasters of the world, (2) patience with passion, (3) patience in obedience to Allah SWT, (4) patience in the difficulty of preaching in the way of Allah, (5 ) patience on the battlefield, (6) patience in association with humans. It is this patient nature that can make a person steadfast in facing various problems of life, from the mild nature to the very severe and complicated problems.Key Words: Education, Children, Family.